Determinan Kinerja Guru di Madrasah Aliyah (MA) Nurul Qur’an: Kepimpinan Kepala Sekolah, Lingkungan Kerja, dan Kompetensi - Angga Susanto; Khotim Fadhli (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of principal leadership, work environment, and competence on teacher performance at Madrasah Aliyah Nurul Qur’an Bendungrejo, Jogoroto, Jombang. The approach used in this study is associative quantitative. Data were collected through questionnaires distributed to 31 teachers at Madrasah Aliyah Nurul Qur’an Bendungrejo. Sampling was carried out using saturated sampling techniques. The results of the study indicate that simultaneously, the variables of principal leadership, work environment, and competence have a significant effect on teacher performance, but partially only the variable of principal leadership does not show a significant effect on teacher performance at Madrasah Aliyah Nurul Qur’an Bendungrejo. This means that schools need to focus more on improving the quality of the work environment and developing teacher competencies to improve teacher performance in the educational process.